Prediction of the metabolizable energy requirements of free-range laying hens - Brainer, M. M. A.; Rabello, C. B. V.; Santos, M. J. B. [UNESP]; Lopes, C. C.; Ludke, J. V.; Silva, J. H. V.; Lima, R. A. (Amer Soc Animal Science, 2016)
This experiment was conducted with the aim of estimating the ME requirements of free-range laying hens for maintenance, weight gain, and egg production. These experiments were performed to develop an energy requirement prediction equation by using the comparative slaughter technique and the total excreta collection method. Regression equations were used to relate the energy intake, the energy retained in the body and eggs, and the heat production of the hens. These relationships were used to determine the daily ME requirement for maintenance, the efficiency energy utilization above the requirements for maintenance, and the NE requirement for maintenance. The requirement for weight gain was estimated from the energy content of the carcass, and the diet's efficiency energy utilization was determined from the weight gain, which was measured during weekly slaughter. The requirement for egg production was estimated by considering the energy content of the eggs and the efficiency of energy deposition in the eggs. The requirement and efficiency energy utilization for maintenance were 121.8 kcal ME/(kg(0.75).d) and 0.68, respectively. Similarly, the NE requirement for maintenance was 82.4 kcal ME/(kg(0.75).d), and the efficiency energy utilization above maintenance was 0.61. Because the carcass body weight and energy did not increase during the trial, the weight gain could not be estimated. The requirements for egg production requirement and efficiency energy utilization for egg production were 2.48 kcal/g and 0.61, respectively. The following energy prediction equation for free-range laying hens (without weight gain) was developed: ME k(cal)/(hen . d) = 121.8 x W-0.75 + 2.48 x EM, in which W = body weight (kg) and EM = egg mass (g/[hen . d]).
Keywords: comparative slaughter; egg production; factorial method